Improvement of Unsafe Act and Unsafe Condition Online Reporting System at Port - Siti Nur Athilah Zolkefli; Zuritah A. Kadir; Abdul Hannan Ensan (Progress in Engineering Application and Technology, 2024)
The port industry is one of the industries that has a high risk of accidents such as overturned trucks, falling into the sea, violations between trucks, overturned forklifts, and etc. Unsafe acts and unsafe conditions is a factor that might cause an accident. Hence, it must be periodically reported and summarised to help the company determine the workplace’s level of safety. The aim of this study was to make an improvement of unsafe acts and unsafe conditions online reporting system. There are three objectives of this study which are to investigate the unsafe act and unsafe condition from online near miss reporting system, to analyse the effectiveness the unsafe acts and unsafe condition online reporting system, and lastly to propose the improvement of unsafe act and unsafe condition online system to top management. In order to achieve the objectives, unsafe acts and unsafe conditions data reporting analysis (existing data) and interview with related representatives will be used to identify problems that need to be analysed and make improvement. Then meeting or group discussion will be conducted to propose to the top management. It was found that the highest near miss accident reported were not wearing PPE with total of 72 cases. Damage equipment recorded 37 cases, Housekeeping involving improper storage issues recorded 24 cases and involving procedure with 22 cases, Traffic involving vehicles park at undesignated parking area reported 15 cases. 18 cases of unsafe conditions involving obstruction of emergency response procedures were reported.